Electronic word of mouth: exploring the consumer perspective - Nasiruddin, Kauthar; Hashim, Haslinda; Raja Yusof, Raja Nerina (IJABM, 2016)
The aim of the paper is to review the phenomena of traditional word of mouth and electronic word of mouth based on consumer behaviour perspective. Customers are increasingly using social media in their purchase decisions. Scholars have shown that positive electronic word of mouth has a significantly positive effect on purchase intention, while negative electronic word of mouth has greater negative impact on purchase intention. This study seeks to examine relevant literature regarding the impact of electronic word of mouth on business and consumers’ behaviour. It is crucial to understand in depth on the impact of electronic word of mouth towards consumption patterns since technology has been widely used in disseminating information.